2012
DOI: 10.1016/j.cej.2012.05.056
|View full text |Cite
|
Sign up to set email alerts
|

Solar photo-Fenton at mild conditions to treat a mixture of six emerging pollutants

Abstract: ElsevierBernabeu García, A.; Palacios Guillem, S.; Vicente Candela, R.; Vercher Pérez, RF.; Arqués Sanz, A.; Amat Payá, AM. (2012). Solar photo-Fenton at mild conditions to treat a mixture of six emerging pollutants. Chemical Engineering Journal. 198-199:65-72. doi:10.1016Journal. 198-199:65-72. doi:10. /j.cej.2012. Highlights Solar photo-Fenton has been able to remove a mixture of six emerging pollutants.  The reaction was performed at acidic and circumneutral media.  Reaction rate was highly influenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 32 publications
2
21
0
3
Order By: Relevance
“…A more economically viable and therefore favourable situation is to operate the process at natural pH since costs associated with the neutralisation of the treated water are avoided and an acidic effluent would not be discharged to the environment. The photo-Fenton process has been reported effective in the removal of micropollutants at natural pH [38,39]. At natural pH the iron photon absorption rate changes with time due to the precipitation of ferric iron, which makes it very difficult to estimate the VRPA.…”
Section: Acetamiprid Degradation At Natural Phmentioning
confidence: 99%
See 1 more Smart Citation
“…A more economically viable and therefore favourable situation is to operate the process at natural pH since costs associated with the neutralisation of the treated water are avoided and an acidic effluent would not be discharged to the environment. The photo-Fenton process has been reported effective in the removal of micropollutants at natural pH [38,39]. At natural pH the iron photon absorption rate changes with time due to the precipitation of ferric iron, which makes it very difficult to estimate the VRPA.…”
Section: Acetamiprid Degradation At Natural Phmentioning
confidence: 99%
“…Iron was added in sequential doses to give a total of 2 and 3 mg Fe/L. The principle behind dosing in this way is to continuously keep a certain amount of iron in solution to be available for photo-Fenton reactions [38]. As occurred at pH 2.8, when iron was added to the system the Fenton reaction with hydrogen peroxide rapidly yielded radicals, which resulted in rapid acetamiprid degradation (Eq.…”
Section: Acetamiprid Degradation At Natural Phmentioning
confidence: 99%
“…However, since the efficiency of AOPs is often case-specific, comparative evaluation of the removal of different pollutants has special importance. Furthermore, since the risk of the formation of oxidation products more toxic than the original parent compounds exists during the application of AOPs [16][17][18][19], careful control of these processes by toxicity test protocols is an essential task.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations have revealed that the degradation of recalcitrant compounds may lead to the creation of harmful solutions (Bernabeu et al, 2012;Pereira et al, 2014;Wu et al, 2009). To evaluate the extent of degradation during the UV/H 2 O 2 /Fe 2þ , UV/ TiO 2 and US processes, the evolution of DXC and dissolved organic carbon (DOC) was determined (Fig.…”
Section: Evaluation Of Antimicrobial Activity Mineralization and Levmentioning
confidence: 99%
“…Photochemical processes can be in turn grouped into heterogeneous and homogeneous catalytic techniques. Of these, photocatalysis with TiO 2 (UV/TiO 2 ) and the photo-Fenton reaction (UV/H 2 O 2 /Fe 2þ ), respectively, are among the most studied (Bernabeu et al, 2012;Lopez-Alvarez et al, 2012. On the other hand, one of the most promising non-photochemical processes is ultrasound (US), which is known to be an environmentally friendly technique due to the absence of chemical additives such as a catalyst or oxidants.…”
Section: Introductionmentioning
confidence: 99%